2016
DOI: 10.1523/eneuro.0020-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increases in proBDNF after Pilocarpine-Induced Status Epilepticus in Mice Are Associated with Reduced proBDNF Cleavage Machinery

Abstract: Brain-derived neurotrophic factor (BDNF) levels are elevated after status epilepticus (SE), leading to activation of multiple signaling pathways, including the janus kinase/signal transducer and activator of transcription pathway that mediates a decrease in GABA A receptor ␣1 subunits in the hippocampus (Lund et al., 2008). While BDNF can signal via its pro or mature form, the relative contribution of these forms to signaling after SE is not fully known. In the current study, we investigate changes in proBDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…In line with previous investigations in epileptic rats [42,[44][45][46] , we demonstrated here the up-regulation of mRNA expressions of p75NTR and pro-NGF in a rat pilocarpine-induced SE model, which in turn is associated with the elevated level of aggressive behavior.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous investigations in epileptic rats [42,[44][45][46] , we demonstrated here the up-regulation of mRNA expressions of p75NTR and pro-NGF in a rat pilocarpine-induced SE model, which in turn is associated with the elevated level of aggressive behavior.…”
Section: Discussionsupporting
confidence: 92%
“…p75NTR levels are elevated after SE in animals and increased activation by proBDNF, like mature BDNF, increases susceptibility to seizures (13,14). Interestingly, our labs have shown that increased synthesis of proBDNF, and not mature BDNF, is the first response of the injured brain in the pilocarpine (PILO) model of epilepsy prior to SEinduced increases of p75NTR (15). This finding suggests that high levels of proBDNF may exert their effects through TrkB rather than p75NTR.…”
Section: Introductionmentioning
confidence: 79%
“…Treatment with antidepressant or antianxiety drugs can restore Bdnf mRNA level in stress-induced model ( Smith et al, 1995 ; Kozisek et al, 2008 ). Although it has been reported that BDNF expression was enhanced in pilocarpine-induced SE ( Thomas et al, 2016 ), BDNF has also been found decreased in patients with chronic temporal lobe epilepsy (TLE) and in animal model of chronic cyclothiazide seizure ( Kong and Cheng, 2014 ; Chen et al, 2016 ). Besides, Xiang et al (2014) pointed out that NBP alleviated cognitive dysfunction in APP mice by BDNF/TrkB/PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%